PENGARUH KEPERCAYAAN, KEAMANAN, PERSEPSI RESIKO DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN SECARA ONLINE MELALUI MEDIA SOSIAL INSTAGRAM - Yuniar Tri Wulandari (JURNAL MANAJERIAL, 2017)
This research aim to analyze and find empirical evidences of Trust, Safety, Perception of Risk, and Service Quality Towards Buying Decision in Instagram. This research used accidental sampling methode to collect the samples. There are 50 students of Muhammadiyah University of Gresik became the participants. The independents variables consist of trust, safety, perception of risk, and service quality. The dependent variable is Buying Decision in Instagram. The multiple regression used to analyze the data of this research. The result showed that trust, perception of risk, and service quality have significant efeect towards buying decision in instagram, but safety has no significant effect towards service quality